Night Fall in the Ti-Tree - Teague, Violet, 1872-1951; Rede, Geraldine (Salt Lake City, UT : Project Gutenberg, 2012)
"Night Fall in the Ti-Tree" by Violet Teague and Geraldine Rede is a children's illustrated poem written in the early 20th century. This book captures the essence of life in the Australian bush, presenting a whimsical and sensitive portrayal of the animals that inhabit it. The likely topic revolves around the themes of nature, the passing of day into night, and the vulnerabilities of wildlife. The poem unfolds with a vivid depiction of twilight in the Ti-tree, where various animals engage in their evening activities. As the sky darkens and sounds of frogs and crickets fill the air, the narrative shifts to the playful existence of rabbits, who are cautioned about the dangers posed by humans. Through enchanting imagery, the poem reflects the joys of nature while also hinting at the perils that threaten the delicate balance of life. The author emphasizes the blend of beauty and danger in the natural world, ultimately encouraging a sense of awareness and appreciation for the animals' plight. (This is an automatically generated summary.)
Wikipedia page about this book: https://en.wikipedia.org/wiki/Night_Fall_in_the_Ti-Tree
Release date is 2012-04-18
E-text prepared by Katie Hernandez, Jason Isbell, Robert Cicconetti, and the Online Distributed Proofreading Team (http://www.pgdp.net) from page images generously made available by International Children's Digital Library (http://en.childrenslibrary.org)
Keywords: Children's poetry, Australian; Rabbits -- Juvenile poetry